Criminal Networks: Who is the Key Player? - Lee, Lung-Fei
We analyze delinquent networks of adolescents in the United States. We develop a theoretical model showing who the key player is, i.e. the criminal who once removed generates the highest possible reduction in aggregate crime level. We also show that key players are not necessary the most active criminals in a network. We then test our model using data on criminal behaviors of adolescents in the United States (AddHealth data). Compared to other criminals, key players are more likely to be a male, have less educated parents, are less attached to religion and feel socially more excluded. They also feel that adults care less about them, are less attached to their school and have more troubles getting along with the teachers. We also find that, even though some criminals are not very active in criminal activities, they can be key players because they have a crucial position in the network in terms of betweenness centrality.Crime; bonacich centrality; betweenness centrality; network characteristics; crime policies